2011
DOI: 10.3390/s110302885
|View full text |Cite
|
Sign up to set email alerts
|

Smart Query Answering for Marine Sensor Data

Abstract: We review existing query answering systems for sensor data. We then propose an extended query answering approach termed smart query, specifically for marine sensor data. The smart query answering system integrates pattern queries and continuous queries. The proposed smart query system considers both streaming data and historical data from marine sensor networks. The smart query also uses query relaxation technique and semantics from domain knowledge as a recommender system. The proposed smart query benefits in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…About 200 to 500 million amputations occur in the world every year due to some factors such as disease, trauma and congenital defects and approximately 80% of it relates to lower extremities ( 2 ). In countries that have recently experienced war, about 80% of amputations is due to war ( 2 , 3 ). During Iraq-Iran war between 1980 and 1988, about 15,000 individuals got severely amputated in upper extremity or lower extremity ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…About 200 to 500 million amputations occur in the world every year due to some factors such as disease, trauma and congenital defects and approximately 80% of it relates to lower extremities ( 2 ). In countries that have recently experienced war, about 80% of amputations is due to war ( 2 , 3 ). During Iraq-Iran war between 1980 and 1988, about 15,000 individuals got severely amputated in upper extremity or lower extremity ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…During Iraq-Iran war between 1980 and 1988, about 15,000 individuals got severely amputated in upper extremity or lower extremity ( 4 ). There are about 11517 veterans with lower extremities amputation in Iran and this number includes different levels of amputation including ankle, upper the knee, knee, lower the knee, and pelvis ( 3 ). Any defect in extremities of the body is not only regarded as a physical injury, but also leads to social and mental-emotional injuries and can affect different life aspects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a broad view of the literature, articles were found that address the use of technological apparatus and present several applications with smart sensors. The works of [2,10,39,41,42,47] describe a view of the application of smart sensors considering the precepts of Industry 4.0, explaining how to integrate IoT with present concepts from Industries 3.0, 2.0 and 1.0. After the inclusion of these works, we defined the bibliographic base of the research, which served as a reference, inspiration, and support for this work.…”
Section: Literature Reviewmentioning
confidence: 99%